Phenotypic Classification and Clinical Examination of Anemia in Iraqi Water Buffalo in Nasiriyah Governorate - Lateaf, Khitam; Allawi, Manar Hadi; Akmoosh, Nuha Jameel (Journal of Buffalo Science, 2023)
This research aims to classify anemia cases in the Iraqi water buffalo population by collecting 140 blood samples from buffaloes in Nasiriyah Governorate pastures. These samples were collected randomly from three age groups: > 1 year, 1-4 years, and < 5 years. Blood sample analysis revealed 45 anemia cases (32.12%) and 95 healthy cases (67.88%). Phenotypic classification of anemia encompassed microcytic hypochromic (12.14%), macrocytic hypochromic (7.85%), normocytic hypochromic (6.42%), and normocytic normochromic (5.71%) cases. Erythrocyte sedimentation rate (ESR) notably increased in anemic buffaloes, displaying a statistically significant disparity (P< 0.05) compared to healthy counterparts. Anemia cases exhibited higher neutrophil counts in white blood cell relative differentials. For the three age groups, hemoglobin (Hb), packed blood cell volume (PCV), and total red blood cell count (RBC) values indicated significant decreases from normal levels, showcasing statistical significance (P< 0.05) between healthy and anemic buffaloes. While anemia cases generally displayed normal iron concentrations, microcytic anemia demonstrated lower iron levels in the 1-4 and >5 years age groups, with iron levels reaching the minimum global normal range in the <1 year age group. Copper concentrations remained normal in all healthy cases and anemia cases, except for microcytic anemia, which showed reduced levels across age groups. In conclusion, this study comprehensively characterizes anemia in Iraqi water buffaloes through clinical, hematological, and elemental analyses. The findings underscore the prevalence of various anemia types, their age-related variations, and significant hematological deviations in anemic buffaloes compared to healthy counterparts. This research enhances our understanding of anemias' impact on this population and provides valuable insights for future diagnostic and management strategies.